2012
DOI: 10.1111/j.1365-2559.2012.04334.x
|View full text |Cite
|
Sign up to set email alerts
|

β‐Catenin and E‐cadherin expression in stage I adult‐type granulosa cell tumour of the ovary: correlation with tumour morphology and clinical outcome

Abstract: Localized variations in adhesion protein expression may partly explain the diverse morphological patterns exhibited by AGCT, and reduced β-catenin staining in primary tumours may have value as an adverse prognostic factor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
(50 reference statements)
2
16
0
Order By: Relevance
“…Stewart et al . identified no nuclear staining with beta‐catenin in 62 ovarian adult granulosa cell tumours . Similarly, Ohishi et al .…”
Section: Discussionmentioning
confidence: 92%
“…Stewart et al . identified no nuclear staining with beta‐catenin in 62 ovarian adult granulosa cell tumours . Similarly, Ohishi et al .…”
Section: Discussionmentioning
confidence: 92%
“…In 2 recent studies, nuclear b-catenin staining was absent in a total of 94 granulosa cell tumors, although membranous and cytoplasmic immunoreactivity was detected in the majority of cases. 19,20 In the study by Maeda and colleagues, investigation and subsequent detection of aberrant nuclear b-catenin staining in 2 MSTs was prompted by the morphologic and immunohistochemical similarity between MST and solid pseudopapillary neoplasm (SPN) of the pancreas and ovary. 2,21,22 We acknowledge this important finding as an impetus to study b-catenin in the current largest available series of MST, but we are of the view that MST is a distinct entity from ovarian SPN.…”
Section: Discussionmentioning
confidence: 99%
“…Sun and colleagues reported that the risk increased when tumours were larger than 13 cm [12]. Recently, reduced β-catenin expression has been associated with a worse disease free survival [19] and warrants further exploration.…”
Section: Prognostic Factorsmentioning
confidence: 97%